Predicting recessions and recoveries in real time: The euro area-wide leading indicator (ALI) - Gabe de Bondt; Elke Hahn (European Central Bank (ECB), 2010)
This study develops a new monthly euro Area-wide Leading Indicator (ALI) for the euro area business cycle. It derives the composite ALI by applying a deviation cycle methodology with a one-sided band pass filter and choosing nine leading series. Our main findings are that i) the applied monthly reference business cycle indicator (BCI) derived from industrial production excluding construction is close to identical to the real GDP cycle, ii) the ALI reliably leads the BCI by 6 months and iii) the longer leading components of the ALI are good predictors of the ALI and therefore the BCI up to almost a year ahead and satisfactory predictors by up to 2 years ahead. A real-time analysis for predicting the euro business cycle during the 2008/2009 recession and following recovery confirms these findings.
Keywords: E32; 330; business cycle; Deviation cycle; euro area; Leading Indicator; Real-time analysis; Wirtschaftsindikator; Frühindikator; Prognoseverfahren; EU-Staaten